"Asking Around": Immigrants' Counterstrategies to Renew Their Residence Permit in Times of Economic Crisis in Italy. Issue 3 (3rd July 2018) - Dimitriadis, Iraklis
ABSTRACT: In contrast to the main body of literature focusing on irregular migrants' counterstrategies, this article explores regular migrant workers' practices to renew their residence permit in an attempt to circumvent structural hurdles due to the restrictive Italian legislative framework. Studying migrants' agency in a socioeconomic context, characterized by high unemployment rates and extensive informal working patterns, I thus distinguish three main counterstrategies: (1) the use of their informal networks to falsify their working relations; (2) the possibility of starting up an individual firm; and (3) taking advantage of structural "loopholes."